Påverkan av torvbrytning på fem vattendrag i Gävleborgs län - Karlsson, Markus (2020)
During the past 20 years, data from five peat mines in north-central Sweden were collected. The analytical results have been compiled into a database. This project aimed at analyzing the data and assessing the environmental impact of peat mining on the recipient waters. Specifically, focus was put on the chemical and physical parameters such as nitrogen, phosphorus, ammonium, organic carbon, pH, alkalinity, conductivity, colour, and suspended material.